Double-Blind, Randomized, Three-Armed, Placebo-Controlled, Clinical Investigation to Evaluate the Benefit and Tolerability of Two Dosages of IQP-AE-103 in Reducing Body Weight in Overweight and Moderately Obese Subjects - Ralf Uebelhack; Udo Bongartz; Stephanie Seibt; Gordana Bothe; Pee Win Chong; Patricia De Costa; Natalia Wszelaki (Hindawi Limited, 2019)
Objective. This study was performed to determine the efficacy and tolerability/safety of IQP-AE-103 on body weight reduction in overweight to moderately obese adults. Methods. A double-blind, randomized, placebo-controlled trial involved one hundred and eight subjects (BMI between 25 and 35 kg/m2) that were randomly assigned to either the low-dose or the high-dose IQP-AE-103 group, or the placebo group. Following a 2-week run-in period, subjects received two capsules of investigational product after three daily main meals for 12 weeks. Subjects were instructed to maintain a nutritionally balanced hypocaloric diet according to the individual's energy requirement. Body weight, body fat, and waist and hip circumference were measured at baseline, and after 2, 4, 8, and 12 weeks. Subjects also rated their feelings of hunger and fullness using visual analogue scales, and food craving on a 5-point scale at the same time intervals. Blood samplings for safety laboratory parameters were taken before and at the end of the study. Results. After 12 weeks of intake, the high-dose IQP-AE-103 group had a significantly greater weight loss compared with the placebo (5.03 ± 2.50 kg vs. 0.98 ± 2.06 kg, respectively; p<0.001) and the low-dose group (3.01 ± 2.19 kg; p=0.001). The high-dose group experienced a decrease in body fat of 3.15 ± 2.41 kg compared with a decrease of 0.23 ± 2.74 kg for the placebo group (p<0.001). High-dose IQP-AE-103 also decreased the feeling of hunger in 66% subjects. A beneficial effect of IQP-AE-103 on the lipid metabolism was also demonstrated in the subgroup of subjects with baseline total cholesterol levels above 6.2 mmol/L. No side effects related to the intake of IQP-AE-103 were reported. Conclusions. These findings indicate that IQP-AE-103 could be an effective and safe weight loss intervention. This trial is registered with NCT03058367.